2006
DOI: 10.2355/isijinternational.46.1635
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Prediction of Lubrication, Powder Consumption, and Oscillation Mark Profiles in Ultra-low Carbon Steel Slabs

Abstract: The flow of melted mold powder into the interfacial gap between the strand and the mold wall is important for productivity and quality in continuous cast slabs. Some of the mold slag (flux) consumption provides true lubrication, while much of the rest is trapped in the oscillation marks on the slab surface. This work presents measurements of powder consumption from extensive careful plant trials on ultra-low carbon steels, and a new, simple, semi-empirical model to predict slag consumption. The model predicts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 37 publications
2
47
1
Order By: Relevance
“…This fact explains why slag consumption has been found to increase with increasing positive strip time in industrial practice. 32) The results also indicate that positive slag infiltration occurs throughout the oscillation cycle but decreases in the second half of the positive strip due to the decrease in liquid film thickness as the solid film recovers. No cases of negative consumption rates were identified in the cycle for the casting parameters studied here.…”
Section: Slag Infiltration and Initial Shell Solidificationmentioning
confidence: 59%
See 2 more Smart Citations
“…This fact explains why slag consumption has been found to increase with increasing positive strip time in industrial practice. 32) The results also indicate that positive slag infiltration occurs throughout the oscillation cycle but decreases in the second half of the positive strip due to the decrease in liquid film thickness as the solid film recovers. No cases of negative consumption rates were identified in the cycle for the casting parameters studied here.…”
Section: Slag Infiltration and Initial Shell Solidificationmentioning
confidence: 59%
“…12 It was also found that the liquid slag thickness increased slightly when descending the mould, which is in agreement with the predictions of Okazawa et al 37) The most remarkable result is the replication of the effect of casting speed on consumption, since it is well known from plant measurements that increases in v c lead to decreases in consumption. However, with exception of the numerical models based in plant data fitting by Meng 16) and Shin,32) or the physical model by Kajitani, 31) this relationship has not been reproduced even qualitatively by previous models.…”
Section: Comparison To Industrial Measurements and Model Limitationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous works 24,26,36) have shed light on the effect of casting speed on fluid flow, heat transfer, and solidification in the mold, but the continuous and associated phenomena are not described, especially at the initial stage of casting process. Figure 12 shows the variations of meniscus level and liquid pool depth measured at a location 40 mm from the mold during the casting process.…”
Section: Evolution Phenomenamentioning
confidence: 99%
“…The predicted flux layer thicknesses were matched with experimental measurements, and a large recirculation zone in the liquid slag pool was observed by these model calculations. Shin et al 26) presented a semi-empirical model, which divided total powder consumption into two components: the lubrication consumption and the flux carried within the volume of oscillation marks, to predict mold lubrication phenomena based on the measurements from extensive plant trials on ultra-low carbon steels. This work was validated by the known trends of oscillation mark depth and slag consumption with various operation parameters, such as mold powder characteristics, casting speed and mold oscillation conditions.…”
Section: Transient Thermo-fluid and Solidification Behaviors In Contimentioning
confidence: 99%